Treatment of moist desquamation for patients undergoing radiotherapy - Raagini Suresh, BS; Jodie Raffi, BA; Florence Yuen, NP; Jenny E. Murase, MD (Wolters Kluwer, 2019)
Moist desquamation occurs in approximately 36% of patients who receive radiation therapy and is associated with severe opioid-resistant pain and discomfort. Moist desquamation is typically at its worst within 1 to 3 weeks after treatment conclusion and resolves over a period of 6 weeks. Herein, we present a therapeutic pearl for the treatment of moist desquamation based on methods from the burn literature, with the goal of helping patients who undergo radiation therapy for breast cancer and other indications. Keywords: Moist desquamation, radiotherapy, radiation, cancer, skin, dressing